2020
DOI: 10.1177/1941738120917932
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in Tensiomyography as Assessed in the Lower Erector Spinae of Healthy Participants: An Observational Study

Abstract: Background: Although there is mounting evidence on sex-linked differences in paraspinal muscle function, it is unknown whether sex-based variations in mechanical and contractile characteristics of the lumbar erector spinae (LES) can be monitored noninvasively in healthy participants at rest using tensiomyography (TMG). Hypothesis: Sex-specific effects in muscle displacement (Dm) and velocity of muscle deformation (Vd) will be observed via TMG assessed in the LES. Study Design: Observational study. Level of Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Given the growing popularity of TMG in research and applied sports science settings, evidence-based recommendations are also required to ensure time-efficient but accurate measurement. The number of trials used in assessment of automated TMG parameters is often not well reported (9,17) or a low number of trials have been used (e.g., 2 trials: (23) and 3 trials: (13)) in some studies. However, it is unclear whether such a low number of trials provides an accurate measurement, especially for V c .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the growing popularity of TMG in research and applied sports science settings, evidence-based recommendations are also required to ensure time-efficient but accurate measurement. The number of trials used in assessment of automated TMG parameters is often not well reported (9,17) or a low number of trials have been used (e.g., 2 trials: (23) and 3 trials: (13)) in some studies. However, it is unclear whether such a low number of trials provides an accurate measurement, especially for V c .…”
Section: Discussionmentioning
confidence: 99%
“…As healthy young adults free from pain were recruited, and the biceps brachii was the only muscle assessed, it is possible that the present findings and recommendations have limited generalizability. Furthermore, given the fact that only 2 female subjects were recruited, the low proportion of female subjects in previous TMG studies (20), and sex-based differences in TMG (23), a potential risk of sex bias exists and the recommendations made in this article should not be indiscriminately generalized to female subjects. Future studies could seek to examine the current research questions with greater sample sizes and in other populations and other muscle groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, myofascial treatment and exercise that can cause muscle fatigue were restricted 48 h before measurement [ 26 ]. To apply the TMG to the participants’ ESM, they were guided to lie face down on the bed and position their legs at 5° flexion using a cushion, and wedge cushions were placed on the ankle and the anterior superior iliac spine (ASIS) to ensure minimal lumbar lordosis [ 27 ]. For accurate measurements, the TMG sensor (GK 40, Panoptik d.o.o., Ljubliana, Slovenia) was perpendicularly placed on a point in the thickest muscle belly marked by a pen upon the ESM’s isometric contraction on the same level as the iliac crest.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, TMG was used to analyze the contractile properties of muscles and was used to assess the mechanical and neuromuscular properties of the ESM, using a TMG sensor with a 0.17 N/mm spring constant [ 27 ]. The TMG involved a 1 ms electrical stimulus (0~100 mA) to elicit the muscle contraction reaction, while the following variables were measured: the maximal displacement (Dm), the time taken to reach 10–90% of Dm (contraction time [Tc]), the time between the initiation of stimulus and 10% of Dm (delay time [Td]), the time of retention between 50% of Dm and 50% of the falling contour (sustain time [Ts]), and the time taken to reach 90–50% of Dm from the falling contour (relaxation time [Tr]) [ 34 ] ( Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%